Moderasi Beragama di Kalangan Milenial Dalam Rangka Merajut Kebinekaan - Kamaludin, Kamaludin; Rahman, Rizki Fachru; Batubara, Raihan Renata; Afriansyah, Yogi; Malahayati, Putri (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The religious moderation campaign for millennial faces many challenges. The facts on the ground show that the phenomenon of radicalism is deeply rooted. The moderation program offered by the government has lost its reputation with the radicalism movement which is packaged attractively and in accordance with current trends. Through a qualitative approach and a radical paradigm of humanism, this study then tries to explore the root cause of the strengthening of radicalism and how complexities are faced by the discourse of religious moderation. This study then found several conclusions including, First, the moderation movement has been less fast and less attractive to millennial compared to the opposite movement. Second, the geneological roots of moderation and radicalism are not finished and are related to the relationship between religion and the post-independence state. Third, the influence of transnational radicalism. Fourth, socio-political-economic factors, including poverty, state violence, legal injustice, political instability, racial issues, militarism and so on. The only opportunity that the discourse of religious moderation has is the preindependence cultural roots, through strengthening cultural values, Islamic treasures (intellectual Islam) and the welfare economic movement. If such opportunities are not utilized, the movement and discourse of religious moderation will run aground in the middle of the road. Keywords: Religious Moderation, Millennials, Islam, radical humanism